2014
DOI: 10.1371/journal.pgen.1004584
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Dopamine-Cholecystokinin Signaling Pathway Shapes Context–Dependent Caenorhabditis elegans Behavior

Abstract: An organism's ability to thrive in changing environmental conditions requires the capacity for making flexible behavioral responses. Here we show that, in the nematode Caenorhabditis elegans, foraging responses to changes in food availability require nlp-12, a homolog of the mammalian neuropeptide cholecystokinin (CCK). nlp-12 expression is limited to a single interneuron (DVA) that is postsynaptic to dopaminergic neurons involved in food-sensing, and presynaptic to locomotory control neurons. NLP-12 release f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(96 citation statements)
references
References 75 publications
10
86
0
Order By: Relevance
“…Furthermore, hyperactive twk-7(null) and kin-2(cau1) mutants are characterized by reduced wave amplitudes during spontaneous crawling. In sharp contrast, hyperactive animals with elevated presynaptic acetylcholine release, such as egl-30(gf) and goa-1(lf) (Brundage et al 1996;Lackner et al 1999;Huang et al 2008), or increased postsynaptic acetylcholine receptor sensitivity (Bhattacharya et al 2014) moved with enhanced wave amplitudes. Although Ga q (gf) and Ga 0 (lf) animals are characterized by an increased spontaneous body-bending frequency on plates, these worms executed futile back-and-forth movements.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, hyperactive twk-7(null) and kin-2(cau1) mutants are characterized by reduced wave amplitudes during spontaneous crawling. In sharp contrast, hyperactive animals with elevated presynaptic acetylcholine release, such as egl-30(gf) and goa-1(lf) (Brundage et al 1996;Lackner et al 1999;Huang et al 2008), or increased postsynaptic acetylcholine receptor sensitivity (Bhattacharya et al 2014) moved with enhanced wave amplitudes. Although Ga q (gf) and Ga 0 (lf) animals are characterized by an increased spontaneous body-bending frequency on plates, these worms executed futile back-and-forth movements.…”
Section: Discussionmentioning
confidence: 97%
“…Plasmids were constructed using the two-slot Gateway Cloning system (Invitrogen) as described previously (Bhattacharya et al, 2014). him-4p::mCD8::GFP Entry vector: A him-4p promoter fragment (2156 bp) was amplified from pPRZ138.2 (a gift from Peter Roy, University of Toronto, ON, Canada) and cloned into pENTR-D-TOPO to create pENTR-3′-him4.…”
Section: Molecular Biologymentioning
confidence: 99%
“…[5][6][7][8] Here we will focus on recent work from our laboratory describing a requirement for the cholecystokininlike neuropeptide NLP-12 in a contextdependent C. elegans foraging behavior. 9 Changes in food availability are among the most variable and challenging environmental factors that animals face. Thus, mechanisms that regulate food-seeking behaviors are particularly important for survival.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that the C. elegans neuropeptide NLP-12, a homolog of mammalian Cholecystokinin (CCK), coordinates behavioral responses to changes in food availability. 9 Specifically, we discovered that NLP-12 signaling is required for behavioral transitions into a local searching motor program that is triggered by removal from food. Immediately following removal from food wild type C. elegans alter their locomotory pattern by increasing high angle turning and restricting movement to their local environment (local or area-restricted search).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation